2022
DOI: 10.1177/23333928221111864
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Healthcare Resource Utilization in Individuals with Major Depressive Disorder

Abstract: Objective To estimate the impact COVID-19 pandemic on healthcare resource utilization (HCRU) among individuals with major depressive disorder (MDD). Method A retrospective cohort study was conducted to compare HCRU in the twelve months prior to and six months following pandemic onset among 1,318,709 individuals with MDD and propensity-score matched controls. Outcomes were monthly rates of all-cause and MDD-specific outpatient, inpatient, and prescription medication HCRU. Piecewise random effects models were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
4
1
Order By: Relevance
“…Despite the rising incidence, we found that the pandemic substantially reduced the use of inpatient and outpatient services among both newly diagnosed and pre-existing patients. This is consistent with the previous studies in South Africa, South Korea, the United States, and the UK, which estimated 15% to 51% reductions in healthcare resource utilization depending on diagnosis settings [ 15 , 17 , 45 , 46 ]. Most of them were conducted during the early phase of the pandemic with a focus on lockdowns.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Despite the rising incidence, we found that the pandemic substantially reduced the use of inpatient and outpatient services among both newly diagnosed and pre-existing patients. This is consistent with the previous studies in South Africa, South Korea, the United States, and the UK, which estimated 15% to 51% reductions in healthcare resource utilization depending on diagnosis settings [ 15 , 17 , 45 , 46 ]. Most of them were conducted during the early phase of the pandemic with a focus on lockdowns.…”
Section: Discussionsupporting
confidence: 93%
“…In the ITS analysis to evaluate changes in depression incidence, we further stratified the analysis into three age groups: adolescents (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), adults (25-64), and the older population (65 +) to explore whether these population subgroups were differentially susceptible to a new depression diagnosis as a result of the pandemic.…”
Section: Subgroup and Sensitivity Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the COVID-19 pandemic overwhelmed the healthcare system of many countries, nearly 20% of mental health centers were closed and 25% introduced limited opening hours during the COVID-19 emergency, an issue further exacerbated by the high percentage of healthcare workers affected by COVID-19 and by the patients' fear of contagion (Heymann and Legido-Quigley, 2022 ). Only urgent psychiatric interventions and mandatory treatments have remained unchanged, while all other activities have been somewhat reduced (Carpiniello et al, 2020 ; Liberman et al, 2022 ). These difficulties in maintaining or obtaining an engagement with psychiatric services could therefore have delayed the treatment of outpatients with MDD.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a large body of literature on the psychological effects of COVID-19, most of it has selected convenient samples and has used non-standardized instruments for the diagnosis [ 18 ]. There is also limited information on the impact on individuals that suffer from depression or other chronic conditions; COVID-19 might have exacerbated pre-existing clinical symptoms in people with MDDs and MS. Another study found an increase in depression severity in patients with MDDs caused by the pandemic, supported by a higher number of hospitalizations of patients with MDDs at a short-term acute care hospital, and all-cause inpatient hospitalizations at a psychiatric facility increased following the pandemic onset and remained elevated throughout the first six months [ 27 ].…”
Section: Introductionmentioning
confidence: 99%